Analisis Strategi Bisnis dan Sistem Informasi Akuntansi terhadap Kinerja UMKM di Sumatera Utara - Neni Marlina Br Purba; Yuliadi; Poniman (LPPM Universitas Putera Batam, 2025)
The objective of this study is to investigate the ways in which business strategies and accounting information systems (AIS) impact the performance of micro, small, and medium enterprises (MSMEs) in North Sumatra both partially and simultaneously. The phenomenon of low MSME performance, which is demonstrated by fluctuating turnover, stagnant profitability, and a lack of competitiveness, is the result of a lack of structured business strategy planning and ineffective use of accounting information systems. A questionnaire was used to collect data, and it was tested for validity and reliability. Selanjutnya, tes klasik asumsi, tes multiple linear regression, tes parsial, dan tes simultan dilakukan dengan menggunakan SPSS.The results indicate that business strategy has a positive and significant impact on SME performance, and SIA also has a positive and significant impact on SME performance. With an adjusted R² coefficient of 0.751, 75.1% of the variation in SME performance can be explained by these two variables, while the remaining 24.9% is influenced by other factors outside the scope of this study. The results indicate that the success of SMEs does not only depend on the right business strategy but also on the effective implementation of SIA to enhance operational efficiency, decision-making speed, and better competitiveness.